HE POISON DIARY OF 1995 Part - 1 - Abd Razak, Dzulkifli (1996)
Poisonings are a significant cause of mortality and morbidity. A 16th century physician, Paracelsus, noted that all substances known to man are poisons, only the amount or dose determines the effect. The course of events below is to remind us that nearly everyone is at risk of acute and chronic toxic exposures to hazardous substances in the ambient environment. The poison diary records, month by month, some of the major events related to poisoning that occurred in 1995. Many of the events cited have been dealt with at some length in this column since April. Based on existing documentation at the National Poison Centre (PRN) in the past one year, it is impossible to list out all the poisoning cases that were handled. Suffice it to say that the following is just the tip of the iceberg.